2015
DOI: 10.18585/inabj.v7i2.77
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study between Thoracic Epidural Anesthesia and General Anesthesia for Patients Who Underwent Modified Radical Mastectomy with Axillary Lymph Node Dissection in De La Salle University Medical Center

Abstract: BACKGROUND: To compare the recovery time and other related clinical outcomes among patients who underwent Modified Radical Mastectomy (MRM) with axillary lymph node dissection under Continuous Thoracic Epidural Anesthesia (CTEA) and General Endotracheal Tube Anesthesia (GETA).METHODS: A retrospective cross-sectional study with 70 patients who underwent MRM in De La Salle University Medical Centre (DLSUMC), categorized into GETA and CTEA group consisted of 35 patients each. Per oral premedications 15 mg midazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Oktavia, [20] found that hypotension (80%) and bradycardia (40%) were more frequent in TE. Lahiri et al [21] found that the incidence of hypotension was 13.3%, and bradycardia was 16.6% in the TE.…”
Section: Discussionmentioning
confidence: 96%
“…Oktavia, [20] found that hypotension (80%) and bradycardia (40%) were more frequent in TE. Lahiri et al [21] found that the incidence of hypotension was 13.3%, and bradycardia was 16.6% in the TE.…”
Section: Discussionmentioning
confidence: 96%